Quand dire, c'est faire l'inverse de ce qu'on dit. Une critique de l'opposition entre théorie et pratique juridiques - Atias, Christian (Les Cahiers de droit, 1987)
This study is based on the following assumption : some legal theories are upset and then turned against the very interests they were supposed to defend. This phenomenon is quite revealing of the nature of the legal process and how legal thinking works. Many explanations have been advanced, however, they all have been rejected since they presume a unity of knowledge and, without proving their point, they assimilate legal reasoning into other sciences that are presented as models for legal thinkers. The upsetting of legal theories may be explained due to the extreme complexity found in the meaning of words used to express legal concepts: this produces a semantic sedimentation with lasting and multiple virtual meanings without there being any way of guessing which one meaning may prevail in any given set of circumstances.